Urbanization effect of mega sporting events using sentinel-2 satellite images: The case of the pyeongchang olympics - Do, Jinwoo; Ahn, Sangho; Kang, Juyoung (Sustainable Cities and Society, 2021)
This study attempts to understand the impact of mega sporting events on local economies by identifying and comparing the urbanization and economic effects of the 2018 Pyeongchang Winter Olympic Games. However, for an accurate evaluation of the effects of hosting the Winter Olympics, it is necessary to consider not only the ripple effect on the local economy but also the increased potential for urban growth from the expansion of social overhead capital. This study calculates the urbanization index and land cover ratio using Sentinel-2 satellite images to examine the urbanization from infrastructure construction for the Pyeongchang Winter Olympics. It additionally analyzes the changes in land price and tax revenue during this period to understand the economic effects of the Olympics, and verifies the correlation between urbanization and economic indicators. The study is unique in that it analyzes the impact of a national event on local communities using satellite image data and presents a comprehensive methodology to understand urban sustainability by monitoring urban changes.
Keywords: Land cover classification; Local economy; Mega sporting event; Olympic games; Olympics; Satellite images; Spectral indices; Sustainable cities; Urban monitoring; Urbanization; Land cover classification; Mega sporting event; Olympic games; Satellite image; Spectral indices; Sustainable city; Urban monitoring; Urbanization